A comparative study on the effectiveness of one-way printed communication versus videophone interactive interviews on health promotion. (January 2016) - Homma, Satoki; Imamura, Haruhiko; Nakamura, Toru; Fujimura, Kaori; Ito, Yoshihiro; Maeda, Yuji; Kaneko, Ikuyo
Introduction: We performed a comparative study of a health education programme that was delivered either through one-way communication with printed media, or through interactive videophone interviews. We aimed to ascertain which mode of counselling, when used in combination with telemonitoring, is more effective at lifestyle modification intended to improve health status. Methods: Participants, who were residents of Kurihara city in Miyagi prefecture, Japan, were randomized into two groups: one group received individualized monthly documented reports ( n = 33; 22 females; average age: 67.2 years), and the other received interactive videophone communication ( n = 35; 22 females; average age: 65.1 years) for three months. Telemonitoring was conducted on both groups, using a pedometer, weighing scale and a sphygmomanometer. Pre- and post-intervention, anthropometric measurements and blood tests were performed; the participants also completed self-administered questionnaires. Results and discussion: The two groups showed similar degrees of health status improvement and satisfaction levels. However, the participants in the videophone group were more aware of improvements in their lifestyles than were the participants in the document group. The individualized printed communication programme was less time-consuming compared to videophone communication. Further studies are needed to formulate a balanced protocol for a counselling-cum-telemonitoring programme that provides optimal health improvement and cost performance with the available human resources.